Public Relations Communication Strategies in Building Consumer Branding: Analysis of Unilever Company - Hermanses, Bintang; Jove, Balqis Tiara; Lukitasari, Mutia Wella (Yayasan Ilomata, 2024)
This article examines the Public Relations (PR) communication strategies employed by Unilever in building and maintaining a strong consumer branding. The study aims to understand how Unilever integrates PR communication strategies and adapts to the digital and social media era to create positive relationships with consumers. The research follows a qualitative approach, utilizing data collection techniques such as market research and consumer trend analysis and utilized a systematic Literature Review (SLR) method. The analysis reveals that Unilever emphasizes transparency, honesty, and consistency in their brand messages and values. They actively engage with consumers through social and environmental initiatives, creating a responsible and caring brand image. The results demonstrate that Unilever's PR strategies have successfully built a strong consumer branding and generated sustainable customer loyalty. The findings have implications for companies seeking to establish a positive and sustainable brand image in a competitive global market.